Working capital management and corporate profitability: the moderating role of foreign ownership - Zhou, Siyu; Amin Noordin, Bany Ariffin; Tunde, Matemilola Bolaji; Chen, Yuhua; Xu, Keming (Elsevier Ltd, 2025)
This study investigates the moderating role of foreign ownership by examining the working capital management (WCM)–corporate profitability relationship in emerging Chinese High-tech manufacturing industry during 2010–2021. We apply a two-way fixed effects model, sub-group testing, and generalised method of moment estimation (GMM), finding that longer Cash Conversion Cycles (CCC) significantly diminish operating profit and shareholder benefits, especially in firms with above-average CCC or high sales growth. Notably, foreign ownership mitigates this negative effect, and this reverse moderating effect is more significant in firms with low WCM efficiency or low growth, suggesting it can enhance corporate governance and ease financial constraints. Managers can bolster profitability by introducing foreign capital, underscoring the strategic role of foreign ownership in emerging markets. The findings enhance the understanding of foreign ownership role in corporate finance and management.